Against Anonymity. (May 2014) - Baker, Robert
Abstract In 'New Threats to Academic Freedom'1 Francesca Minerva argues that anonymity for the authors of controversial articles is a prerequisite for academic freedom in the Internet age. This argument draws its intellectual and emotional power from the author's account of the reaction to the on‐line publication of ' After‐birth abortion: why should the baby live?'2 – an article that provoked cascades of hostile postings and e‐mails. Reflecting on these events, Minerva proposes that publishers should offer the authors of controversial articles the option of publishing their articles anonymously. This response reviews the history of anonymous publication and concludes that its reintroduction in the Internet era would recreate problems similar to those that led print journals to abandon the practice: corruption of scholarly discourse by invective and hate speech, masked conflicts of interest, and a diminution of editorial accountability. It also contends that Minerva misreads the intent of the hostile e‐mails provoked by 'After‐birth abortion, ' and that ethicists who publish controversial articles should take responsibility by dialoguing with their critics – even those whose critiques are emotionally charged and hostile.